Education, Gender, and Family Formation - Hanna Virtanen; Mikko Silliman; Tiina Kuuppelomäki; Kristiina Huttunen (Institute of Labor Economics (IZA), 2024)
We study the effect of educational attainment on family formation using regression discontinuity designs generated by centralized admissions processes to both secondary and tertiary education in Finland. Admission to further education at either margin does not increase the likelihood that men form families. In contrast, women admitted to further education are more likely to both live with a partner and have children. We then pre-register and test two hypotheses which could explain each set of results using survey data. These suggest that the positive association between men's education and family formation observed in the data is driven by selection. For women, our estimates are consistent with the idea that, as increased returns to social skills shift the burden of child development from schools to parents and particularly mothers, education can make women more attractive as potential partners.
Keywords: J13; I26; 330; family; education; gender